The Emerging Application of Itaconate: Promising Molecular Targets and Therapeutic Opportunities - Lin, Jiaqi; Ren, Jinxuan; Gao, Dave Schwinn; Dai, Yi; Yu, Lina (Frontiers in Chemistry, 2021)
Metabolites have recently been found to be involved in significant biological regulation and processes. Itaconate, an important intermediate metabolite isolated from the tricarboxylic acid cycle, is derived from cis-aconitate decarboxylation mediated by immune response gene 1 in the mitochondrial matrix. Itaconate has emerged as a key autocrine regulatory component involved in the development and progression of inflammation and immunity. It can directly modify cysteine sites on functional substrate proteins related to the inflammasome, signal transduction, transcription, and cell death. Itaconate can also act as a connector among immunity, metabolism, and inflammation, which is of great significance for obtaining a deeper understanding of the mechanisms of cellular immune metabolism. It is also a potential option for the treatment of inflammation and immune-related diseases. This paper presents a systematic review of the potential mechanisms of action of metabolites associated with different pathological conditions. We briefly summarize the structural characteristics and classical pathways of itaconate and its derivatives, with special emphasis on its potential for future clinical application, in order to provide a theoretical basis for future research and treatment intervention.